2018
DOI: 10.1007/s13340-018-0366-y
|View full text |Cite
|
Sign up to set email alerts
|

Histone demethylases regulate adipocyte thermogenesis

Abstract: Adipocytes play a pivotal role in the regulation of energy metabolism. While white adipocyte stores energy, brown adipocyte dissipates energy by producing heat. In addition, another type of heat-producing adipocyte, beige adipocyte, emerges in white adipose tissue in response to chronic coldness. This phenotypic adaptation to the cold environment is considered to be attributed to the epigenetic modifications. Histone methylation is a chemically stable epigenetic modification and thus a proper mechanism for lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 32 publications
(66 reference statements)
0
7
0
Order By: Relevance
“…Histone methylation is chemically stable and thus may act as a longterm cell memory mechanism. Several enzymes that regulate methylation of histone lysine residues, notably members of the lysine (K)-specific demethylase (KDM) family, are involved in the control of beige adipocyte metabolism 129 . The most studied family member is KDM1A, which activates a beiging programme while repressing WATspecific genes by interacting with the thermogenic transcription factors ZFP516 and PRDM16 [130][131][132] .…”
Section: Energy Dissipationmentioning
confidence: 99%
“…Histone methylation is chemically stable and thus may act as a longterm cell memory mechanism. Several enzymes that regulate methylation of histone lysine residues, notably members of the lysine (K)-specific demethylase (KDM) family, are involved in the control of beige adipocyte metabolism 129 . The most studied family member is KDM1A, which activates a beiging programme while repressing WATspecific genes by interacting with the thermogenic transcription factors ZFP516 and PRDM16 [130][131][132] .…”
Section: Energy Dissipationmentioning
confidence: 99%
“…Further, with the acknowledged role of adipose tissue in the maintenance of metabolic homeostasis and altered adipogenesis associated with the MetS, studies have been undertaken to understand better the role of epigenetic processes in regulating the adipocyte function in the setting of such metabolic disorders [ 23 , 27 , 28 ]. A recent study by Daniel et al [ 23 ] identified global DNA methylation of LINE-1 to be associated with metabolic deterioration and glucose metabolism in visceral adipose tissue of individuals with and without MetS.…”
Section: The Classical Epigenetic Mechanisms In Metsmentioning
confidence: 99%
“…Alterations in histone modifications are identified as essential components of epigenetic networks, controlling energy homeostasis and altering adipocyte thermogenesis, thereby contributing to the pathogenesis of MetS ( Table 2 ) [ 28 , 41 ]. For example, a study involving mice deficient in histone demethylase, HDM2a, an enzyme responsible for H3K9 demethylation, reported the development of adult-onset obesity, hypertriglyceridemia and hypercholesterolemia, as well as insulin resistance (IR), in the deficient mice as compared to the wild type [ 41 ].…”
Section: The Classical Epigenetic Mechanisms In Metsmentioning
confidence: 99%
“…Brown adipocyte originates from sub-population of dermomyotome precursors expressing Myf5, Pax7, and engrailed 1 (En1). This dermomyotome precursor cell differentiates into either brown preadipocyte which expresses early B cell factor (EBF2) or MyoD-expressing myoblast [1,5,14]. The nature of precursor cells of beige adipocyte is more complicated as is reported that the concept of beige adipocyte does not include only one identical type of thermogenic cells, but encompasses diverse types of thermogenic cells which emerge in white adipose tissue and possibly in other organs in response to the external stimuli [1,15].…”
Section: White Brown and Beige Adipose Cell Fatementioning
confidence: 99%
“…coldness). Indeed, recent studies have revealed that the cell fate of beige adipocyte is regulated by diverse histone methyl-modifying enzymes such as JMJD3 (also known as KDM6B) [22], euchromatic histone-lysine Nmethyltransferase 1 (EHMT1) (also known as GLP) [23], Jumonji domain containing 1A (JMJD1A) (also known as JHDM2A or KDM3A) [24], and LSD1 (also known as KDM1A or AOF2) [25,26] (reviewed in [5,14]) ( Table 1).…”
Section: Histone Demethylases As Regulators Of Beige Adipogenesismentioning
confidence: 99%